New Perspective in Atrial Fibrillation - Guenancia, Charles (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In spite of the large volume of associated research, the pathophysiological mechanisms involved in atrial fibrillation (AF) onset and recurrence remain uncertain. This may explain why the performances of thromboembolic and bleeding prediction scores in AF patients are limited. In the past few years, the concept of atrial cardiopathy has emerged as a promising lead to connect AF to stroke, heart failure, and inflammatory processes: indeed, all of the mechanisms associated with atrial remodeling and the development of atrial cardiopathy are also likely to promote the development of AF. This recent concept of atrial cardiopathy suggests that the real trigger of stroke may be an abnormal atrial substrate rather than atrial rhythm itself. In this setting, AF could be seen as a symptom of atrial cardiopathy rather than a risk factor of stroke. In the absence of validated clinical markers of atrial cardiopathy, the search for the mechanism of AF remains the cornerstone of cardioembolic stroke prevention for now.The aim of this Special Issue is to gather basic research as well as pathophysiological and epidemiological papers focused on the relationship between atrial substrates and atrial fibrillation onset, recurrence, and outcomes.